The Contribution of Social Media Promotion Towards Participants' Interest to Join the Permata Sakti National Virtual Run 2020 - Ilman Zuda Septiawan; Rumini Rumini; Billy Castyana (Indonesian Journal of Sport Management, 2023)
This is a descriptive quantitative research using survey methods. The researchers took data from a questionnaire filled out by participants in the Permata Sakti National Virtual Run 2020. Respondents filled out a questionnaire in google form with a 4-point Likert scale which has variables, namely social media as a promotional medium, interaction between social media users, social media as brand equity, media social as a brand attitude, and the participant's decision to take part in the championship. Data from 39 respondents were then analyzed using Spearman Rank in the IBM SPSS Statistics 25 application and these results were also supported by a SWOT analysis of related scientific articles. Based on the data obtained, it can be seen that participants have an age range of 14-65 years with the majority of social media used is Whatsapp and Instagram. Data also shows that promotion using social media in the event has a significance value of 0.749 which means it has a strong relationship and the level of influence is 69.8%. These results are also supported by the results of the SWOT analysis where the use of social media is considered efficient and flexible in spreading promotions because easy and fast.